Effects of Mind Mapping Combined with Microvideo Explanation on Disease Perception Control and Nursing Cooperation during Membrane Induction Therapy in Patients with Infectious Nonunion after Tibial Trauma - Rui Xiong; Ni Wang; JingXuan He (Emergency Medicine International)
Objective. To study the effects of mind mapping combined with microvideo explanation on disease perception control and nursing cooperation during membrane induction therapy in patients with infectious nonunion after tibial trauma. Methods. 30 patients with infectious nonunion after tibial trauma treated in the hospital between March 2018 and March 2022 were selected as the research subjects, and the patients were divided into a control group (n = 15) and an observation group (n = 15) by the random number table method. During membrane induction therapy, the control group adopted a routine nursing method while the observation group was given a nursing method of mind mapping combined with microvideo explanation. The disease perception control, nursing cooperation, and self-care ability of the two groups of patients were compared. Results. After nursing, the scores of aspects of “life impact (3.87 ± 0.92),” “duration (3.20 ± 1.01),” and “emotions (3.93 ± 0.59)” of the Brief Illness Perception Questionnaire (B-IPQ) in the observation group were lower than those in the control group (5.27 ± 0.88, 4.67 ± 1.05, and 4.93 ± 0.80, respectively) (P<0.05) while the scores of “self-control (6.80 ± 1.21)” and “disease awareness (7.27 ± 0.70)” were higher than those in the control group (5.00 ± 1.07 and 5.93 ± 0.70, respectively) (P<0.05). There was no significant difference in the total compliance rate between the two groups (P>0.05). After nursing, the scores of dimensions and the total score of the Exercise of Self-Care Agency Scale (ESCA) were increased in the two groups, and the scores were higher in the observation group than those in the control group (P<0.05). Conclusion. Mind mapping combined with microvideo explanation can improve the disease perception control during membrane induction therapy in patients with infectious nonunion after tibial trauma, improve the self-care ability, and facilitate the smooth progress of treatment.